Rhodium(III)‐Catalyzed Enantioselective Coupling of Indoles and 7‐Azabenzonorbornadienes by C−H Activation/Desymmetrization. (7th December 2018) - Yang, Xifa; Zheng, Guangfan; Li, Xingwei
Abstract: Chiral rhodium(III) cyclopentadienyl catalysts (Cp X Rh III ) play significant roles in asymmetric arene C−H activation. Rh/Ir‐catalyzed couplings of arenes and strained rings have been well‐studied, but they have been limited to racemic systems. Reported in this work is the Cp x Rh III /AgSbF6 ‐catalyzed enantioselective desymmetrizative C−C coupling of N ‐pyrimidylindoles and 7‐azabenzonorbornadienes with high efficiency and enantioselectivity. The role of AgSbF6 has been established by mechanistic studies. AgSbF6 enhances the catalytic activity by suppressing the C3−H activation of the indoles, activation which would otherwise lead to catalytically inactive species.